Design and prototype of an external quality assurance program for urine bicarbonate - Benjamin, Ryan (Division of Chemical Pathology, 2014)
This dissertation validates a Beckman-Coulter DxC(R) assay for total bicarbonate in urine and then proceeds to design, prototype and cost an inter-laboratory comparison (ILC) program for the above urine bicarbonate based on the validation. Furthermore, this work serves as a case study for how to establish proficiency testing - and thereby achieve accreditation - for tests without external quality assurance because of analyte instability.